Finite Element Analysis and Ultrasonic Evaluation of Stresses in Q345 Plates - Zhu, Yuhong; Tan, Jidong; Song, Cheng (IOP conference series. Materials Science and Engineering, 2020)
This paper investigates and demonstrates the nondestructive capability of ultrasonic waves and magnetic Barkhausen noise (MBN) in stress evaluation of Q345 plates. A 10mm thick Q345 specimen was subject to a concentrated load by a stressing jack, known as three-point bending test. A finite element model of Q345 plate was established to verify the experimental results. The stresses have been measured by three nondestructive evaluation methods including ultrasonic techniques, magnetic Barkhausen noise method and strain gauge method. This paper gives the details of development of ultrasonic longitudinal critically refracted (LCR) wave based technique for stress measurement. The results show great agreement between finite element and three stress measurements which are accomplished nondestructively.